MARKETING COMFORT IN USING PUBLICLY SOCIAL MEDIA DATA - Tiara Ramadhani (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
As technology advances, entrepreneurs will have more options to use social media as a marketing platform for their businesses. Although social media platforms have shown to be beneficial to businesses in terms of better understanding what customers and the general public have to say about their products or services, not all customers are comfortable with such approaches. It is related to consumers' belief and expectation that digital platforms will protect their personal private data, so it is also necessary to establish boundaries to ensure that consumers are comfortable with the marketing ethics that marketers utilize when using publicly available social media data. The data was analyzed using multiple linear regression after 61 social media users in Jakarta completed a questionnaire. The findings will reveal the variables that influence the relationship between consumers' marketing comfort and marketers' ethical marketing practices while using publicly available social media data. The R-sq 85,30 percent indicates that all variables have a significant effect on marketing comfort. This study can help marketers make decisions and get insight by using publicly available social media data to alleviate customer concerns and provide convenience about data in the business based on ethical marketing information.